Isolation and Purification of Thermostable β-Mannanase from Paenibacillus illinoisensis ZY-08 - Lee, Y.S., Dong-A University, Busan, Republic of Korea; Zhou, Y., Dong-A University, Busan, Republic of Korea; Park, I.H., Dong-A University, Busan, Republic of Korea; Subhosh Chandra Muni Ramanna Gari, Dong-A University, Busan, Republic of Korea; Ahn, S.C., Pusan National University, Busan, Republic of Korea; Choi, Y.L., Dong-A University, Busan, Republic of Korea (Applied biological chemistry, 2010)
A bacterium, ZY-08 that produced extracellular mannanase, was isolated and identified as Paenibacillus illinoisensis (P. illinoisensis) on the basis of 16S rDNA phylogenetic analysis. The enzyme was purified to apparent homogeneity by ultrafiltration, DEAE-Sepharose chromatography, and Sephadex G-50 chromatography procedures. The β-mannanase was purified 3.5 fold to homogeneity with a final recovery of 22% and specificity of 9.3 U/mg protein as judged by SDS-polyacrylamide gel electrophoresis. The molecular mass was about 60 kDa. It was active at 60℃ and pH 6.0 and it's retained about 40% of activity at 70℃, with a broad pH range of 3.0-6.0. The mannanase was highly specific towards glucomannan and galactomannan, but exhibited very low activity towards starch, carboxy-methyl cellulose, and birchwood xylan. Result of thin-layer chromatography analysis showed that the enzyme produced various kinds of oligosacchrides. These unique properties of the thermostable mannanase and broad substrate specificity (low activity towards cellulosic substrates) from P. illinoisensis ZY-08 make this enzyme attractive for biotechnological applications.